Citrus Pest Quick Guide: Diaprepes Root Weevil - Lauren M Diepenbrock; Jamie D Burrow (EDIS)
A one-page quick guide written by Lauren M. Diepenbrock and Jamie D. Burrow and published by the Entomology and Nematology Department presents the life cycle of the Diaprepes root weevil and provides several photos of the pest and the damage it causes to assist in identification. https://edis.ifas.ufl.edu/in1249